ITEM ANALYSIS FOR GRATITUDE QUESTIONNAIRE 6 ITEMS (CQ-6) - Clara Moningka; Annisa Windi Soewastika (Universitas Mercu Buana Jakarta, 2023)
Gratitude is an important part of human life that can affect many things. In this study, the researcher analyzed the GQ6 (Gratitude Questionnaire-six items) from Emmons, et.al which consists of four facets and is measured by six items. This scale measures the extent to which individuals feel grateful in terms of intensity, density, span, and frequency. This research involved 300 respondents who are residents of the greater areas of Jakarta. Reliability testing was carried out with Cronbach's alpha. The results of this study indicate that gratitude or GQ6 meets construct validity.